GEOMORPHOLOGIC CHANGES IN THE COASTLINE OF VISTONIS LIKE, THRACE, Ν GREECE. - Δελημάνη Π.; Ξειδάκης Γ. (Bulletin of the Geological Society of Greece, 2018)
The lake Vistonis is a shallow coastal lake about 20 km SE of the city of Xanhti; in Greek Thrace. It constitutes one of the most important hydrobiotope of Thrace. The lake has an area 45χ106 m 2 and a total volume of water 106*106 m . It accepts today around 330.000 m 3/yr sediments and a total volume of 360><106 m3/sec fresh water from the surrounding basin. Due to human intervention to drainage system of the basin i.e. entrenchment of the torrent channels and diversion of their courses (river Kosinhtos),etc, the solid load reaching the lake increased a lot during the last decades resulting in the increase sedimentation inside the lake. As a result the rate of the lake shrinkage increased. Besides that the lake suffer from eutrophication due to fertilizers brought with river waters. In this paper the changes in the lake’s shoreline the last 170 year is discussed. As it is shown the lake’s coastline exhibits prograduction (advance) at its north and east side and erosion and retreat at the south and west side. This is attributed to the distribution of the incoming sediment and to the prevailing, in the area, NE and SE winds.